Investigating the Relationship between Demographic Variables And Emotional Intelligence and Spiritual Health in the Nurses Working in the Teaching Hospitals of Ilam - Rohollah Yarbeigi; Arman Azadi; Yousef Veisani; Seyed Rahmatollah Mousavimoghadam (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: There is a close relationship between a nurse’sinherent spirituality and the tendency toprovide spiritual care. This means that anurse with stronger inherent spirituality provides more spiritualcare to patients. The aim of this study was to investigate the relationship between demographic variablesand emotional intelligence and spiritual health in the nurses working in the teaching hospitals of Ilam city.Materials and Methods: This was a descriptive-analytical study onthe nurses working in the teachinghospitals ofIlam. The research sample included all the nurses of teaching hospitals ofIlamcity, who wereselected by census. The research instrument includedthree questionnaires;a demographic questionnaire (age,gender, marital status, work experience, and employment status), a 20-item spiritual health questionnaire, andthe 90-item standard Barquestionnaire for emotional intelligence. The spiritual health questionnaire, alreadyvalidated by Tavan et al.,included 20 questions infour dimensions (five questions for each of contemplation,beliefs, morality, and philosophy/lifestyledimensions). Finally, the data was entered into and analyzed bySPSS version 19 software.Results: This descriptive study was conducted on 130 nurses working in the teaching hospitals of Ilam. Ofthese, 79 (60.8%) and 51 (39.2%) were males and females, respectively. The mean spiritual health scoreswere obtained as 23.72, 21.98, 22.68, and 22.47 in the contemplation, beliefs, morality, and philosophy/lifestyledimensions, respectively, with the total score of 90.86. The total score of emotional intelligencewas 313.34. Among the nurses, 7 (5.4%), 115 (88.5%), and 8 (6.2%) had moderate, high, and very highemotional intelligence, respectively.Conclusion: The nurses’ spiritual health was at the moderate-high level for all the participants, and it can bepromoted by implementing education programs.